Crop Insurance in Nepal: Farmers’ Perception on Paddy Crop Insurance and Institutional Performance in Chitwan and Bardiya Districts - Ghimire, Shiva Sundar; Shrestha, Shiddi Ganesh; Panta, Hari Krishna; Sharma, Govinda Prasad; Sigdel, Udit Prakash (NPRC Journal of Multidisciplinary Research, 2026)
Background: The Government of Nepal has implemented subsidized agriculture and livestock insurance for more than one decade. However, the penetration rate of crop insurance in farming communities seems to be very slow. Therefore, this study explored farmers’ perceptions of the paddy crop insurance scheme and institutional effectiveness in implementing the paddy crop insurance scheme.Objectives: The objectives of this study were to examine farmers’ attitudes toward paddy crop insurance and to assess perceptions of the effectiveness of institutional roles.Methods: The research adopted a mixed method using both qualitative and quantitative data. Total 460 respondents were selected, having equal numbers of insured and non-insured. Primary data was gathered using a semi-structured interview schedule. Descriptive and exploratory techniques were used for the analysis of data. Chi-square tests, and composite indexing models were applied using SPSS and Stata.Findings: The results show that farmers appreciated the government's initiative, they were dissatisfied with claim procedures, compensation, and institutional support. Key barriers included complex documentation, claim settlement, low awareness, and poor coordination among implementing agencies.Conclusion: The study concludes that weak institutional performance and low trust in insurance companies limit the effectiveness and uptake of paddy crop insurance. Strengthening institutional roles, simplifying procedures is critical to enhance adoption and ensure better risk management.Novelty: This study adds to the body of knowledge on agricultural insurance in Nepal by comparing the districts of Chitwan and Bardiya and investigating how farmers view institutional performance and paddy crop insurance. The results provide evidence at the district level regarding the ways in which institutional service delivery and farmer risk perception impact crop insurance program participation.